Opowiesci Szekspirowskie : adapcja klasycznej wersji - Lamb, Charles, 1775-1834.; Toman, Karel; Lamb, Mary, 1764-1847.; Shakespeare, William, 1564-1616. (Warszawa : Elipsa, 1994)
The plays of Shakespeare adapted by Charles Lamb into stories and translated into Polish. For teenagers.
Keywords: Shakespeare, William, -- 1564-1616 -- Adaptations